2013
DOI: 10.1002/hup.2297
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional potential of mephedrone: an analysis of the subjective effects

Abstract: By having similar subjective effects as MDMA and other entactogens, mephedrone seems able to substitute other enactogenic stimulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 30 publications
1
29
1
2
Order By: Relevance
“…For example, only 28.9% of 4MMC users reported that subjective effects of 4MMC and cocaine were “very similar” or “nearly the same,” whereas 36% reported that 4MMC and cocaine effects were only “somewhat similar” or “not similar at all” (Kapitány-Fövény et al, 2013). Furthermore, of 4MMC users who also previously used 3,4-methylenedioxymethamphetamine (MDMA) and cocaine, twice as many users responded that 4MMC effects were more comparable to MDMA than cocaine (Carhart-Harris et al, 2011).…”
Section: Effects Of a 4-methyl Substituentmentioning
confidence: 99%
“…For example, only 28.9% of 4MMC users reported that subjective effects of 4MMC and cocaine were “very similar” or “nearly the same,” whereas 36% reported that 4MMC and cocaine effects were only “somewhat similar” or “not similar at all” (Kapitány-Fövény et al, 2013). Furthermore, of 4MMC users who also previously used 3,4-methylenedioxymethamphetamine (MDMA) and cocaine, twice as many users responded that 4MMC effects were more comparable to MDMA than cocaine (Carhart-Harris et al, 2011).…”
Section: Effects Of a 4-methyl Substituentmentioning
confidence: 99%
“…Synthetic cathinones (a.k.a. : “bath salts”) are of particular concern because some drugs in this class (e.g., mephedrone, methylone) have served as replacements for ecstasy (Carhart-Harris et al, 2011; Kapitány-Fövény et al, 2013). While effects of some synthetic cathinones are reportedly similar to effects of ecstasy or other stimulants (Brunt et al, 2011; Carhart-Harris et al, 2011), use has been associated with many adverse health outcomes (Miotto et al, 2013; Zawilska and Wojcieszak, 2013; Zawilska and Andrzejczak, 2015), including over 20,000 ED visits in the US in 2011 (SAMHSA, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…As impulsivity -and especially sensation seeking -usually rise during adolescence [36], for this age group it is thought to be more relevant to focus on the immediate and short-term consequences of substance use, not only on the long-term risks of recurrent psychoactive substance consumption. All the presented somatic and psychological effects are based on the findings of former studies [37][38][39][40]. These effects are indicated by the red dots located on a picture of a schematic body with the option to touch a dote on the screen (see Figure 4) and so access detailed description of the effects.…”
Section: Trans-formation: Somatic and Psychological Effects Of Pychoamentioning
confidence: 99%